The language culture of the personality: psychology and pedagogical bases of the studying and formation (Actual Problems of Psychology in Educational Institutions, 2018)
The article deals with the results of the studying of the language culture of a personality as the psychological phenomenon. Functions, structurally informative and operational characteristics of this phenomenon have been described. The language culture peculiarities of junior students with speech disorders and those who are with normal speech development are investigated. The relation between the components of language culture formation and academic achievement in language subjects have been revealed. The data can be used by educators and psychologists to predict aptitude to low language culture.
Keywords: language culture of the personality; post-modern socio-cultural-interdeterministic dialogic approach; speech mental and emoyional componets; method of contrasting groups; children with normal speech development; children with speech disorders; academic achievement